Case Report of Xanthogranulomatous Pyelonephritis: A Rare Diagnostic in Pediatric Aged Patients - Gonçalves,Carolina Ferreira (2023)
ABSTRACT Xanthogranulomatous pyelonephritis is an unusual variant of chronic pyelonephritis in which there is massive destruction of the renal parenchyma by granulomatous tissue. The pathophysiological mechanism is not yet fully understood, and the diagnosis is challenging. This is a rare and sporadic diagnosis in the pediatric population. Here, we report a case of a 2-year-old girl with a one-year history of urinary tract infections and recurrent cloudy urine with traces of sand. Several urinalyses demonstrated pyuria without bacteria growth, and she was admitted to the pediatric nephrology unit. Imaging tests were performed and a xanthogranulomatous pyelonephritis was diagnosed. After confirmation of functional exclusion of the right kidney, a successful right nephrectomy was performed, and the histology confirmed the diagnosis. This case highlights the importance of complementary tests, in a child with signs and symptoms of urinary tract dysfunction, to exclude any pathology requiring therapeutic intervention.